Examining the Impact of Murabahah Financing at BMT Berkah Madani on Development Micro, Small and Medium Enterprises (MSMES) - Muhammad Bayu Lesmana; Mega Octaviany; Ahmad Sandi (Al-Mashrafiyah (Jurnal Ekonomi, Keuangan dan Perbankan Syariah), 2024)
The aim of this research is to examine the impact of Murabahah financing on the development of MSMEs. The research method employed a quantitative approach. Primary data was collected through the distribution of questionnaires to 100 customers of BMT Berkah Madani, while secondary data was obtained from literature, journals, and BMT Berkah Madani's data. The population of this study consisted of BMT Berkah Madani customers who applied for Murabahah financing. Non-probability sampling was used as the sampling method. The collected data was processed using SPSS Version 27. The findings of the research indicate a significant relationship between Murabahah financing and the development of MSMEs, with a correlation coefficient value of 0.786 and a coefficient of determination of 0.618, demonstrating a strong and significant influence of Murabahah financing on the development of MSMEs.